Follower Behavior and Followership Identity: A Follower’s Perspective - Heise, Scott (Kansas State University. K-State Libraries, 2018)
This research evaluated how people who have functioned as followers understood their role as a follower and how their followership attitude shaped their behavior in that role. From 13 in-depth qualitative interviews, followers expressed their ideas from a follower’s perspective and viewed their roles on a spectrum from “humble compliance” to “shared responsibility for organizational outcomes.” All but one participant was unfamiliar with the term followership, and when asked to define the term, responses ranged from “no idea”, to “a partnership with leadership”. None of the participants had considered that their identities as followers could be developed in a similar manner to leadership development to improve relationships and role expression. Qualitative methods were employed to capture the nuanced responses that would not have been possible through surveys or questionnaires. Participant responses were analyzed to capture language and behavioral expressions in context. This research employed open coding to examine, categorize, compare, and conceptualizing themes that inform future research populations and variable selection.
Citation: Heise, S. (2018) Follower Behavior and Followership Identity: A Follower’s Perspective. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Non-Freshman Category, grand prize
Keywords: Followership; Follower behavior; Followership development; Leadership development